Corporate Tax Planning Strategies: The Role of Shell Companies in Tax Havens and Their Impact on Emerging Markets - Saratian, Eko Tama; Murtopo, Purno; Yulianto, Imam Dwi; Pahala, Indra; Handaru, Agung Wahyu (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines tax planning strategies employed by multinational corporations, focusing on the role of shell companies in tax havens and their impact on emerging markets. Using a systematic literature review approach, the research explores various tax planning techniques such as transfer pricing, profit shifting, and the utilization of international tax treaties to optimize tax liabilities. The findings indicate that these practices contribute to significant tax revenue losses in emerging economies, affecting fiscal stability and economic growth. Despite the implementation of international regulations such as the OECD’s Base Erosion and Profit Shifting (BEPS) initiative to curb tax avoidance, multinational corporations continue to adapt with new strategies. This study recommends enhancing tax transparency, strengthening international cooperation, and reforming tax policies in emerging markets to mitigate the adverse effects of corporate tax avoidance.